2014
DOI: 10.14257/ijseia.2014.8.1.12
|View full text |Cite
|
Sign up to set email alerts
|

How Human Aspects Impress Agile Software Development Transition and Adoption

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 52 publications
0
44
0
1
Order By: Relevance
“…This part of the findings seemed to have a good potential to be studied more in detail by receiving more data. However, later this part reached to a proper maturity level [16]. This part of the findings also showed that people-related issues (team members and managers involved the transition) strongly affect the transition.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This part of the findings seemed to have a good potential to be studied more in detail by receiving more data. However, later this part reached to a proper maturity level [16]. This part of the findings also showed that people-related issues (team members and managers involved the transition) strongly affect the transition.…”
Section: Discussionmentioning
confidence: 66%
“…[11,16], in this paper only addresses the most important points regarding to the adopted research methodology.…”
Section: Fig 1 Multi-level Coding In Gtmentioning
confidence: 99%
“…Motivated members try to deal with the emerging challenges and find the best strategies to cope with them. Also, having Agile Champions, those who can persuade others to be Agile by their behaviors, promotes and facilitate Scrum adoption as well as other Agile methods [18,22,23].…”
Section: Team Members' Motivationmentioning
confidence: 99%
“…For instance, in some studies, training has been addressed as serious facilitator to cope with the adoption related issues [6], [7]. Furthermore, selection of talented people and taking advantages from full-time mentoring services were reported as other supporting factors to avoid the challenges of Scrum and other Agile methods adoption [8], [9]. However, in all studies there were no specific process for people nomination and hiring appropriate and talented experts for conducting the adoption process.…”
Section: Introductionmentioning
confidence: 99%